2011
DOI: 10.1002/rra.1372
|View full text |Cite
|
Sign up to set email alerts
|

Tree colonization trends on a sediment bar after a major flood

Abstract: Tree mortality and regeneration in riparian areas are greatly influenced by flooding. The elevational distribution of Salix spp. and Robinia pseudoacacia were investigated by observing densities and standing conditions before and after a major flood on a sediment bar in the middle reaches of the Arakawa River in Kumagaya, Japan. The subsequent tree recruitment was also examined. R. pseudoacacia was easily washed away with the eroded sediment, whereas Salix spp. was found to be more tolerant. Both species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…Therefore, while the flushing of vegetation is one of the most important processes that is used to produce these vegetative structures, its succession is based on an alteration of sediment characteristics, such as its nutrient condition in the basic process. Asaeda et al (2010) and Asaeda et al (2011b) reported that the colonization of two dominant tree species in the Ara River floodplain of Japan, namely Salix spp. and R. pseudoacacia, is determined by a difference in the tolerance of each species to flooding-induced sediment mobilization.…”
Section: Laboratory Analysesmentioning
confidence: 98%
“…Therefore, while the flushing of vegetation is one of the most important processes that is used to produce these vegetative structures, its succession is based on an alteration of sediment characteristics, such as its nutrient condition in the basic process. Asaeda et al (2010) and Asaeda et al (2011b) reported that the colonization of two dominant tree species in the Ara River floodplain of Japan, namely Salix spp. and R. pseudoacacia, is determined by a difference in the tolerance of each species to flooding-induced sediment mobilization.…”
Section: Laboratory Analysesmentioning
confidence: 98%
“…Robinia pseudoacacia and Albizia julibrissin. Details are given in Asaeda et al (2009Asaeda et al ( , 2011. Figure 2 were taken before and after the flood that the great flood caused by Typhoon No.…”
Section: The Kumagaya Section Of the Arakawa Rivermentioning
confidence: 99%
“…From the field observation by Asaeda et al (2011), the criteria was obtained for the surviving trees after the 2007 flood and the scouring depth of the ground surface. It is obtained such that 50% of the trees are lost if the scour depth is 0.5 m, and all trees are washed away if the scour depth is 1.0 m or more, as is shown in Fig.…”
Section: Vegetation Washout Modelmentioning
confidence: 99%
“…One of the major disruptions that needs to be considered in fluvial environments is the successive effect of floods on forest stands. Frequent floods and heavy flooding are dominant factors in the dynamics and structure of riparian stands [20,21]. It is known that heavy floods can cause considerable destruction of trees.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is recognized that the flood regime and sediment mobility are responsible for the configuration of channels, floodplains and riparian vegetation [22,23]. Furthermore, the physiological characteristics of forest communities may indeed vary depending on soil and sediment properties, as well as the microtopography of the riverbanks, which are gradually shaped by successive floods [18,21,24].…”
Section: Introductionmentioning
confidence: 99%